Enhanced pinning property by inserted Si seed layer - KOMAGAKI KOUJIRO; NISHIOKA KOUICHI (2014)
The embodiments of the present invention generally relate to a magnetic head having a silicon seed layer disposed between a lower shield and a metallic underlayer to enhance the unidirectional anisotropy in an antiferromagnetic layer disposed over the metallic underlayer.